Actualization of Pancasila Values through Religious Moderation based on Islamic Boarding school (Pesantren) Education - Hengki Koes Meiran (Jurnal Indonesia Studi Moderasi Beragama, 2024)
Nowadays, many new radical and separatist ideologies are a challenge for the Indonesian people. The reality of religious radicalism in Indonesia is increasingly troubling, especially after the reformation. The purpose of the research is to reveal pesantren education in actualizing the values of Pancasila through religious moderation in the Pesantren of Bengkulu City. This type of descriptive qualitative research is used to examine how pesantren teach santri (students) to live the values of civil society through religious moderation. The results of research on pesantren education in actualizing the values of Pancasila through religious moderation are that moderation education in the learning curriculum of Islamic boarding schools can be one way to maintain the values contained in Pancasila. In addition to the existence of religious moderation education, other spiritual activities can also shape human moral personality so that it can become a harmonious and peaceful being. The contribution of this research is as a novelty and enrichment material both theoretically and practically related to the urgency of pesantren education in actualizing Pancasila values through religious moderation.